Crecimiento y supervivencia de larvas de Echinometra lucunter (Echinoidea: Echinometridae) alimentadas con las microalgas Chaetoceros gracilis e Isochrysis galbana - Astudillo, David (2005)
Larval growth and survival of Echinometra lucunter (Echinoidea: Echinometridae) fed with microalgae Chaetoceros gracilis and Isochrysis galbana. Thirty sexually mature sea urchins (Echinometra lucunter; diameter 45.8 ± 17.5 mm) were collected at Macanao, Margarita Island, Venezuela (11°48’29” N / 64°13’10” W). They were injected potassium chloride (50 M) directly into the celomic cavity. After two minutes 90% spawned (17 females and 10 males), the others never spawned. Fertilization was 87.0 ± 12.6% (1:100 oocytes/sperm) at 29 ± 2ºC. The fertile eggs were placed in three treatment gropsu with nine containers (18 liters; 2 eggs/ml) each, all with bottom aeration. Treatments were: Chaetoceros gracilis; Isochrysis galbana, and a mixture of both microalgae (respectively: 20 000 and 60 000 cell/ml for each microalgae, 1:1 for the mixture). Salinity, pH, temperature and larval survival were determinated daily. The study ended when the post-metamorphic phase was completed. The embryonic development time was 16.3 ± 0.2 h until the prism stage at pH 8.4 ± 0.1; 38 ± 1 psu and 28 ± 1.4°C. The two-arms larval stage was reached at 24 h: 33 min, with a total length of 190 ± 16.3 μm fed on C. gracilis, 152 ± 19.0 μm with I. galbana and 182.4 ± 14.1 μm with the mixture. The larvae next to metamorphosis reabsorbed the arms and had the characteristic shape of juvenile urchins at 12 days with 670.2 ± 22.2 μm fed on C. gracilis, 665 ± 12.1 μm fed on I. galbana and 670 ± 14.1 μm fed on the mixture. The accumulated survival to the juvenile stage was 14.7 ± 3.8% when fed on C. gracilis, higher than the other treatments (5.4 ± 1.2; 14.0 ± 2.6). E. lucunter is an excellent prospect to be commercially cultured because of its short embryonic (16 hours) and larval development time (12 days) and good survival rate when fed on monoculture (C. gracilis and I. galbana) or mixed diet (we recommend C. gracilis). Rev. Biol. Trop. 53(Suppl. 3): 337-344. Epub 2006 Jan 30.